Cleaning Nanoceria Particles by Diluted HNO3 with H2O2 Mixture (NPM) Solution at Different Temperatures. (1st January 2023) - Wang, Yingjie; Wu, Bingbing; Qiu, Li-Na; Hu, Lianfeng; Cheng, Haijun; Qu, Xin-Ping; Hamada, Satomi; Wada, Yutaka; Hiyama, Hirokuni
Abstract : It is difficult to remove nanoceria abrasives from the SiO2 substrate after the shallow trench isolation (STI) chemical mechanical polishing process. In this work, we studied the cleaning behavior of ceria particles by using an acidic cleaning solution instead of normal sulfuric acid and hydrogen peroxide mixture solution (SPM) at high temperatures (above 85 °C) and low temperatures (below 30 °C). The solution, named as NPM, consists of HNO3 (1–2 vol%), H2 O2 (5–10 vol%), and deionized water (DIW). It is found that NPM can dissolve nanoceria particles at high temperatures with higher cleaning efficiency (CE) than that of SPM. NPM can clean the A90 (90 nm ceria) particles under ultrasonic/megasonic at low temperatures, while SPM has poor CE at 20 °C. The redox reaction of NPM and its effect on cleaning mechanism were systematically studied.